Arms and Goods Embargo in International Practice "the Case of Libya " - Bouriah, Faiza (Journal of Legal Studies and Researches, 2022)
In 2011, Libyans joined the Arab Spring revolutions and soon turned into an armed conflict that the United Nations identified as a threat to international peace and security in the region, a number of resolutions were adopted including economic sanctions such the arms embargo in 2011and oil smuggling in 2014, in order to stifle the warring parties and force them to negotiate, but it hasn’t worked till today. Libyans to join.